FIR laser lines from CH3OD: A review - De Michele, A.; Carelli, G.; Moretti, A.; Pereira, D.; Costa, L. F.; Cruz, F. C.; Moraes, João Carlos Silos [UNESP] (Kluwer Academic/plenum Publ, 2004)
The methanol isotopic species CH3OD has also proved to be an efficient and powerful medium to generate radiation in the far infrared (FIR) region. After the critical review of 1994, six papers have been published dealing with new FIR laser lines from this molecule. As a consequence of the use of wide tunability waveguide CO2 lasers as well as a new pulsed CO2 laser operating at hot and sequential bands, as of optical pumping sources, the total number of the FIR laser lines increased from 122 in 1994 to 227 today. In this communication we present an updated and complete catalogue of FIR laser lines generated from CH3OD. Information on wavelength, offset, relative polarization, intensity, and optimum operation pressure is generally available.
Keywords: FIR laser lines; CH3OD; methanol's isotope